Exclusion of fish and invertebrates from benthic patches of artificial aquatic environments across water conductivity levels using high-frequency (10 Hz) pulses and adjustable electrical settings - Utz, R. M.; Cooper, S. D.; Gido, Keith B.; Stewart, J. R. (My University, 2017)
Livestock fence chargers are often used to generate pulsed electrical fields in freshwater environments to exclude fish and invertebrates from benthic patches so that their ecological function can be investigated. Such devices appear to be effective, but the precise characteristics of the electrical fields they generate and specific settings needed to exclude organisms across water conductivity levels have not been described. We present an electrical engineering and experimental framework to predict and evaluate the effectiveness of a modified device at different combinations of electrical settings and water conductivities. We avoided toxic materials and considered safety issues. We conducted laboratory experiments to identify the electrical fields with a 10-Hz pulse frequency needed to exclude adult Fathead Minnows (Pimephales promelas) and crayfish (Procambarus clarkii) from electrical exclosures across a range of water conductivities (13-800 S/cm). Fish and crayfish in waters of low conductivity (550 S/cm) were excluded from exclosures at >= 200 V of electric potential. In water of higher conductivity (>= 250 S/cm), similar settings caused consumer immobilization. Electrical pulse durations of 150 1.ts were more effective than 50-gs pulse durations at excluding organisms. Further refinement toward standardized methods requires analogous experimentation in the field, but our findings emphasize the importance of comprehensively considering electrical fields (voltage, pulse frequency and duration), water conductivity, and electrode configuration a priori when using these devices to optimize designs.
Citation: Utz, R. M., Cooper, S. D., Gido, K. B., & Stewart, J. R. (2017). Exclusion of fish and invertebrates from benthic patches of artificial aquatic environments across water conductivity levels using high-frequency (10 Hz) pulses and adjustable electrical settings. Freshwater Science, 36(1), 151-161. doi:10.1086/690599
Keywords: Electrical Exclosure; Conductivity; Procambarus Clarkia; Pimephales; Promelas; Tropical Stream